2006
DOI: 10.1210/en.2005-1331
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Perinatal Undernutrition Alters Neuronal and Neuroendocrine Differentiation in the Rat Adrenal Medulla at Weaning

Abstract: Epidemiological studies suggest that chronic adult diseases, such as type 2 diabetes and hypertension, can be programmed during fetal and early postnatal life. The nervous system regions governing vegetative functions and the hypothalamic-pituitary-adrenal axis are particularly sensitive to the perinatal nutritional status. Despite recent reports demonstrating that the activity of the sympathoadrenal system can be altered by early life events, the effects of maternal nutrient restriction on the adrenal medulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 44 publications
6
24
1
Order By: Relevance
“…Undernutrition during gestation and lactation induces changes in the development of adrenal chromaffin cells, resulting in increased catecholamine levels at weaning (34,35). We have also observed that maternal protein restriction only during lactation programs for high catecholamine synthesis and secretion at adulthood (22).…”
Section: E946supporting
confidence: 53%
“…Undernutrition during gestation and lactation induces changes in the development of adrenal chromaffin cells, resulting in increased catecholamine levels at weaning (34,35). We have also observed that maternal protein restriction only during lactation programs for high catecholamine synthesis and secretion at adulthood (22).…”
Section: E946supporting
confidence: 53%
“…Additionally, neural regulation of PNMT is mediated by splanchnic nerve innervation as part of the SA system (Kvetň anský & Pacák 1995). It is suggested that the SA system can also be programmed for development of hypertension, with subsequent effects within the adrenal medulla, such as enhanced activity of chromaffin cells as early as 1 week of age (Molendi-Coste et al 2006). Thus, increased activity of adrenal chromaffin cells may be dependent on dysregulation of either one or both the HPA and SA axes.…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamine content of the plasma was determined as previously described in detail using high-performance liquid chromatography coupled with electrochemical detection after alumina extraction (29). Plasma glucagon content was determined with a commercial available enzyme-linked immunosorbent assay (ELISA) kit (Glucagon Quantikine; R&D Systems).…”
Section: Plasma Assaysmentioning
confidence: 99%